Arbuscular Mycorrhizal Fungus Enhances Lateral Root Formation in Poncirus trifoliata (L.) as Revealed by RNA-Seq Analysis - Chen, Weili; Li, Juan; Zhu, Honghui; Xu, Pengyang; Chen, Jiezhong; Yao, Qing (Frontiers in Plant Science, 2017)
Arbuscular mycorrhizal fungi (AMF) establish symbiosis with most terrestrial plants, and greatly regulate lateral root (LR) formation. Phosphorus (P), sugar, and plant hormones are proposed being involved in this regulation, however, no global evidence regarding these factors is available so far, especially in woody plants. In this study, we inoculated trifoliate orange seedlings (Poncirus trifoliata (L.) Raf) with an AMF isolate, Rhizophagus irregularis BGC JX04B. After four months of growth, LR formation was characterized, and sugar contents in roots were determined. RNA-Seq analysis was performed to obtain the transcriptomes of LR root tips from non-mycorrhizal and mycorrhizal seedlings. Quantitative real time PCR (qRT-PCR) of selected genes was also conducted for validation. The results showed that AMF significantly increased LR number, as well as plant biomass and shoot P concentration. The contents of glucose and fructose in primary root, and sucrose content in LR were also increased. A total of 909 differentially expressed genes (DEGs) were identified in response to AMF inoculation, and qRT-PCR validated the transcriptomic data. The numbers of DEGs related to P, sugar, and plant hormones were 31, 32, and 25, respectively. For P metabolism, the most up-regulated DEGs mainly encoded phosphate transporter, and the most down-regulated DEGs encoded acid phosphatase. For sugar metabolism, the most up-regulated DEGs encoded polygalacturonase and chitinase. For plant hormones, the most up-regulated DEGs were related to auxin signaling, and the most down-regulated DEGs were related to ethylene signaling. PLS-SEM analysis indicates that P metabolism was the most important pathway by which AMF regulates LR formation in this study. These data reveal the changes of genome-wide gene expression in responses to AMF inoculation in trifoliate orange and provide a solid basis for the future identification and characterization of key genes involved in LR formation induced by AMF.